Femoral Bone Marrow Insulin Sensitivity Is Increased by Resistance Training in Elderly Female Offspring of Overweight and Obese Mothers - Ville Huovinen; Marco Bucci; Heta Lipponen; Riku Kiviranta; Samuel Sandboge; Juho Raiko; Suvi Koskinen; Kalle Koskensalo; Johan G Eriksson; Riitta Parkkola; Patricia Iozzo; Pirjo Nuutila (United States, 2025)
Abstract
-
Bone marrow insulin sensitivity may be an important factor for bone health in addition to bone mineral density especially in insulin resistant conditions. First we aimed to study if prenatal maternal obesity plays a role in determining bone marrow insulin sensitivity in elderly female offspring. Secondly we studied if a four-month individualized resistance training intervention increases bone marrow insulin sensitivity in elderly female offspring and whether this possible positive outcome is regulated by the offspring’s mother’s obesity status. 37 frail elderly females (mean age 71.9 ± 3.1 years) of which 20 were offspring of lean/normal-weight mothers (OLM, maternal BMI ≤ 26.3 kg/m2) and 17 were offspring of obese/overweight mothers (OOM, maternal BMI ≥ 28.1 kg/m2) were studied before and after a four-month individualized resistance training intervention. Nine age- and sex-matched non-frail controls (maternal BMI ≤ 26.3 kg/m2) were studied at baseline. Femoral bone marrow (FBM) and vertebral bone marrow (VBM) insulin sensitivity were measured using [18F]fluoro-2-deoxy-D-glucose positron emission tomography with computer tomography under hyperinsulinemic euglycemic clamp. We found that bone marrow insulin sensitivity was not related to maternal obesity status but FBM insulin sensitivity correlated with whole body insulin sensitivity (R = 0.487, p = 0.001). A four-month resistance training intervention increased FBM insulin sensitivity by 47% (p = 0.006) only in OOM, while VBM insulin sensitivity remained unchanged regardless of the maternal obesity status. In conclusion, FBM and VBM glucose metabolism reacts differently to a four-month resistance training intervention in elderly women according to their maternal obesity status.